Analysis of furan and its major furan derivatives in coffee products on the Chinese market using HS-GC–MS and the estimated exposure of the Chinese population. (1st September 2022) - Cao, Pei; Zhang, Lei; Yang, Yang; Wang, Xiao-dan; Liu, Zhao-ping; Li, Jian-wen; Wang, Li-yuan; Chung, Sookja; Zhou, Moqin; Deng, Ke; Zhou, Ping-ping; Wu, Ping-gu
Highlights: Improved HS-GC–MS method is simpler to operate and had better applicability. Coffee beans and coffee power were the products with the highest contents of furan and its derivatives. Furan and 2-methylfuran were the residues with the highest detection rates and contents in coffee products. Research on the control of furan and its derivatives in the production process of coffee products should be strengthen. Abstract: The current study analysed concentrations of furan and its derivatives in coffee products commercially available in China based on an improved headspace gas chromatography-mass spectrometry (HS-GC–MS) method and estimated health risks. A total of 101 samples of coffee products on the Chinese market was analysed. Furan (98%, ND-6569 μg/kg) and 2-methylfuran (100%, 2–29639 μg/kg) were the compounds with the highest concentrations and detection rates in coffee products. The mean dietary exposure of Chinese consumers to furan and the sum of furan, 2-methylfuran and 3-methylfuran in coffee products was 0.09 and 0.46 μg/kg bw/day, respectively. For the neoplastic effects of furan, the margin of exposure (MOE) was 14, 556 for the mean dietary exposure of consumers. For the non-neoplastic effects of furan, MOEs were 711 and 139 for furan and the sum of furan, 2-methylfuran and 3-methylfuran, respectively. Overall, a health concern is indicated for coffee consumers with MOEs below 10000.